Frequency and persistency of DNA vaccine encoding GP25 by oral on common carp - Nuryati, Sri; Yuliyanti, ,; Alimuddin, , (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT Koi herpesvirus (KHV) is a major viral pathogen that infects common carp and koi. KHV disease outbreak is happened in almost all centre of common carp culture in Indonesia and caused mass mortality. Deoxyribonucleic acid (DNA) vaccination method is one of ways to cope with KHV infection. Vaccines were commonly given by injection. The aim of this research was to get frequency and persistency of DNA vaccine encoding GP25 given by oral delivery method in common carp. This research would like to determine dose, frequency of vaccination, persistency of DNA vaccine and culture medium for the bacterial host. DNA vaccine persistency test was done by using polymerase chain reaction (PCR) method with the specific primer for GP25 gene. The results showed that level of DNA vaccine that could be detected in feed was 7.56 ng (equal to 1.598×1010 copies). Efficient culture medium for Escherichia coli DH5α carrying DNA vaccine was LB triptone. Feeding fish with diet supplemented with 1 mL E. coli DH5α containing DNA vaccine for each fish and two times a week allowed persistence of DNA vaccine in kindney and spleen. Keywords: common carp, KHV, DNA vaccine, GP25, persistance  ABSTRAK Koi herpesvirus (KHV) adalah virus patogen utama yang menginfeksi ikan mas dan ikan koi. Wabah penyakit KHV terjadi di hampir semua sentra budidaya ikan mas di Indonesia dan menyebabkan kematian massal ikan. Metode vaksinasi DNA merupakan salah satu cara yang dapat dilakukan untuk menanggulangi serangan KHV. Pemberian vaksin umumnya dilakukan dengan cara injeksi. Tujuan penelitian ini adalah untuk menguji frekuensi dan persistensi vaksin DNA GP25 antivirus KHV yang diberikan melalui oral pada ikan mas. Pada penelitian ini dilakukan uji dosis, frekuensi pemberian vaksin, persistensi vaksin DNA, dan media kultur bakteri inang. Persistensi vaksin DNA dianalisis menggunakan metode PCR dengan primer spesifik gen GP25. Hasil penelitian menunjukkan bahwa dosis vaksin DNA yang dapat terdeteksi dalam pakan adalah 7,56 ng (setara dengan 1,598×1010 copy). Media kultur yang efisien bagi bakteri Escherichia coli DH5α pembawa vaksin DNA adalah LB tripton. Pemberian pakan bervaksin berupa bakteri konsentrasi 1 mL/ekor ikan dengan frekuensi dua kali seminggu menghasilkan persistensi DNA GP25 di ginjal dan limpa. Kata kunci: ikan mas, KHV, vaksin DNA, GP25, persistensi